Chronic Cavitary Pulmonary Aspergillosis with Divergent Clinical Courses: A Case Series of Two Patients Presenting with Recurrent Hemoptysis - Suci Guntari; Darmawan Ismail; Grace Thandekire Sibande; Oke Dimas Asmara (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Chronic pulmonary aspergillosis (CPA) is a progressive, potentially life-threatening fungal infection of the lungs. Its management is complicated by comorbidities, chronicity, and diagnostic uncertainty. While antifungal therapy remains the cornerstone of treatment, surgical intervention is indicated in selected cases, especially those presenting with hemoptysis or suspicion of malignancy. Multidisciplinary evaluation and perioperative optimization are crucial, particularly in elderly or complex patients. Case: We described two patients with CPA who exhibited divergent clinical courses. Both were refractory to medical therapy and ultimately underwent surgical intervention. Thoracotomy revealed extensive necrotic cavities with high fungal burden, and histopathology confirmed chronic cavitary pulmonary aspergillosis. Debridement and postoperative antifungal therapy led to significant clinical improvement in both cases. These experiences highlight critical decision points in CPA management, including patient selection for surgery, intraoperative flexibility, and postoperative monitoring. Conclusion: Surgery remains an essential component of comprehensive CPA management, particularly when medical therapy fails or diagnostic uncertainty persists. Integrating surgical and pharmacological strategies through multidisciplinary collaboration ensures optimal outcomes, even in elderly or immunocompetent patients. Carefully timed and individualized surgical intervention provides both diagnostic confirmation and symptomatic relief in cases of advanced or refractory CPA.